Gender-based violence and femicide interventions-perspectives from community members and activists in South Africa - Mkwananzi, Sibusiso; Nathane-Taulela, Motlalepule (Frontiers in Global Women's Health, 2024)
Globally, Gender-Based Violence and Femicide (GBVF) remains a multifaceted social issue in the 21st century. Despite the ratification of international treaties and national laws, South Africa continues to have alarmingly high levels of GBVF, which were worsened during the Covid-19 national lockdown. The 2020 crime statistics reported that one in five South African women were victims of GBVF and South African Police Services (SAPS) data from 2015 to 2020 showed that seven women are killed daily nationwide. Despite copious studies on GBVF, the voices of local community members and activists as key collaborators in such research have been excluded. Therefore, this study used a mixed methods approach to determine the known interventions to decrease or eliminate GBVF and their effectiveness in seven communities across South Africa. The study included 191 participants in a survey for the quantitative aspect as well as a qualitative aspect of the study. Community members participated in gender-specific focus group discussions, while activists had a focus group of their own to obtain data on interventions. Our findings showed that three main forms of interventions existed in South Africa, viz. government-led campaigns that normally occurred during the 16 days of activism against violence towards women and children, community-led campaigns in response to GBVF cases reported in the media as well as NGO-led initiatives to support GBV survivors. However, these interventions were stifled by the social and cultural stigma against reporting GBVF, a lack of sustainability, decreased visibility, poor organisation and management as well as a lack of funding. Therefore, our findings show that while the South African government has made strides in its efforts to eliminate GBVF, there are no sustainable community level programming and interventions aimed at changing social norms and toxic masculinity that perpetuate GBVF. In conclusion, we recommend that efforts be made to implement intervention initiatives that go beyond creating awareness on GBVF, but partner with local NGO-led organizations to engage in programming and intervention that is aimed at changing social norms.